A semente da colonização: um estudo sobre a Colônia Agrícola Benevides (Pará, 1870-1889) - NUNES, Francivaldo Alves (Universidade Federal do Pará, 2013)
This dissertation focuses on the agricultural colonization in the State of Pará (Brazil) in the last decades of the nineteenth-century, taking as reference the locality of Benevides. It examines not only the interests concerned in the ways of occupation, the principles which presided over the selection of the colonial areas, the types of planting, size and distribution of the land, but also the way the settlers understood these processes. Thus, we assume that the occupation of these colonies reflected the relationship between the laws and official measures designed to manage them, and the way of life adopted by the settlers themselves.